Thiamine responsive megaloblastic anemia: a novel SLC19A2 compound heterozygous mutation in two siblings. Issue 5 (4th January 2013) - Mozzillo, Enza; Melis, Daniela; Falco, Mariateresa; Fattorusso, Valentina; Taurisano, Roberta; Flanagan, Sarah E; Ellard, Sian; Franzese, Adriana
Abstract : Thiamine responsive megaloblastic anemia (TRMA) is an autosomal recessive disease caused by loss of function mutations in the SLC19A2 gene. TRMA is characterized by anemia, deafness, and diabetes. In some cases, optic atrophy or more rarely retinitis pigmentosa is noted. We now report two sisters, the eldest of which presented to a different hospital during childhood with sensorineural deafness, which was treated with a hearing prosthesis, insulin requiring diabetes, retinitis pigmentosa, optic atrophy, and macrocytic anemia. These features initially suggested a clinical diagnosis of Wolfram syndrome (WS). Therapy with thiamine was initiated which resulted in the resolution of the anemia. The younger sister, who was affected with sensorineural deafness, was referred to our hospital for non‐autoimmune diabetes. She was found to have macrocytosis and ocular abnormalities. Because a diagnosis of TRMA was suspected, therapy with insulin and thiamine was started. Sequencing analysis of the SLC19A2 gene identified a compound heterozygous mutation p.Y81X/p.L457X (c.242insA/c.1370delT) in both sisters. Non‐autoimmune diabetes associated with deafness and macrocytosis, without anemia, suggests a diagnosis of TRMA. Patients clinically diagnosed with WS with anemia and/or macrocytosis should be reevaluated for TRMA.